Chinese Medicinal Herbs Targeting the Gut–Liver Axis and Adipose Tissue–Liver Axis for Non-Alcoholic Fatty Liver Disease Treatments: The Ancient Wisdom and Modern Science - Zhang, Shuwei; Wong, Yui-Tung; Tang, Ka-Yu; Kwan, Hiu-Yee; Su, Tao (Frontiers in Endocrinology, 2020)
Non-alcoholic fatty liver disease (NAFLD) is one of the most common causes of chronic liver disease worldwide. The pathogenesis of NAFLD is complex. Recent studies reveal that the gut-liver axis and adipose tissue-liver axis play important roles in the development of NAFLD. The frontline western medicine may fail to treat the NAFLD patients. Nevertheless, the uniqueness of Chinese medicine in its interpretation of NAFLD and the holistic therapeutic approach lead to a promising therapeutic efficacy. With advanced technology, the ancient wisdom of the Chinese medicine can be interpreted by modern pharmacological studies. Furthermore, many herbal formula are found to target the gut-liver axis and adipose tissue-liver axis and resolve the inflammation in NAFLD. This is the first review summarizes the current findings on the Chinese herbal formula that are targeting the two axis for NAFLD treatment. This review provides valuable information for the further development of the herbal-based treatment for NAFLD.